Responses of the stratified flows to their driving conditions-A field study - Yuksel, Yalcin; Ayat, Berna; Ozturk, Mehmet Nuri; Aydogan, Burak; Guler, Isikhan; Cevik, Esin Ozkan; Yalciner, Ahmet Cevdet (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
The Bosphorus is oceanographically very complicated two-layer stratified strait where denser water from the Marmara Sea flows towards North under the lighter water which is frequently flowing from the Black Sea towards South. The water level difference between both ends of the Bosphorus varies seasonally within the range of -0.2 and 0.6 m. The seasonal variability depends mainly on the water level changes in the adjacent basins related to the hydrological cycle, short-term changes in the atmospheric pressure and the wind characteristics. These variations together with the depth and alignment of the cross section along the strait dominate the spatial and temporal variations and sometimes sharp changes in the flow pattern in three dimensions. Although these hydrodynamic conditions are critical for all marine and hydraulic works along the Bosphorus, there was riot continuous long-term measurement for a sufficient time span in the strait for detailed evaluation of the current climate. An extensive site surveying work including current, wind, pressure and water level measurements was carried out between September 2004 and January 2006 in relation to the design and construction requirements of the Bosphorus Tube Crossing Project. In this study, the characteristics of stratified flow in the Bosphorus Strait and their relation to local and regional, short- and long-term changes in the meteorological parameters are studied by using the measurement data and the results are discussed comparatively. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: stratified flows; density currents; strait flows; the Bosphorus; current climate; STRAIT; Engineering; Oceanography